Potential of Tithonia diversifolia Hemsley A. Gray (Kembang Bulan) Leaf Extract as Anti-Cancer Agents - Muflihah Rizkawati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
The main objective of this review is to explain the great potential of herbal plants as anticancer agents. Cancer is a disease caused by abnormal cell growth in the body. The high number of cancer incidents still become a global concern because of the high mortality rate. The treatments of cancer such as chemotherapy can cause serious side effects by killing the normal cells. This is the reason why it is necessary to develop an alternative treatment of cancer. I discussed a plant that is believed to has health benefit. Many studies have showed the positive effect of Tithonia diversifolia plant for health. After 2000, the researchers discovered a new potential through its cytotoxicity to neoplastic cells. This plant needs to be developed sustainably. However, in the future this plant might become an effective alternative to treat cancer with lower side effects.